2004
DOI: 10.1007/s00401-003-0818-7
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal dementia with ubiquitinated neuronal inclusions presenting with primary lateral sclerosis and parkinsonism: clinicopathological report of an autopsy case

Abstract: We report a case displaying upper motor sign, parkinsonism, and behavioral abnormality, with marked degeneration of the precentral cortex, neostriatum and frontotemporal lobes, as well as ubiquitinated neuronal inclusions. The patient was a 66-year-old male at the time of death. At age 57, he noticed progressive difficulties in speaking and swallowing. At age 60, he was severely anarthric and displayed emotional lability and incontinence. Neurologically, very poor movement of tongue was observed, but without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…To date, cases of FTLD with ubiquitin-positive, tau-negative inclusions (previously called as FTLD-U) showing CST degeneration but lacking both LMN loss and Bunina bodies have been reported not only from our institution but from other institution in Japan [28,31]. The disease duration of these two cases was 9 years [28] and 11 years [31], respectively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To date, cases of FTLD with ubiquitin-positive, tau-negative inclusions (previously called as FTLD-U) showing CST degeneration but lacking both LMN loss and Bunina bodies have been reported not only from our institution but from other institution in Japan [28,31]. The disease duration of these two cases was 9 years [28] and 11 years [31], respectively.…”
Section: Discussionmentioning
confidence: 94%
“…The CST is involved in various brain diseases such as cerebrovascular diseases or degenerative diseases, and the latter is not limited to MND [17][18][19][28][29][30][31][32]. In contrast to the cerebrovascular diseases, CST degeneration in the degenerative diseases is often more severe at lower than at higher levels, and is thought to arise from axonopathy with peripheral "dying back" [29,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…They also show that unlike neurons the quantitative assessment of these inclusions may be a neuropathological marker of disease duration. The presence of ubiquitin-positive tau-negative intraneuronal inclusions within the cerebral cortex and subcortical structures has been long considered as a key neuropathological feature of MND with dementia [16,45] or FTD with MND [3,5,7,9,11,17,23,27,31,39,42,46]. Despite several contributions based on small series, the presence of ubiquitin-related pathology within the cerebral cortex is still considered a rare phenomenon in typical FTD cases [2,6,15,18,21,22,24,34,35,40,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Although a global understanding of the molecular background of FTD is far from being achieved, one can schematically consider that this group includes a large but poorly defined subgroup of typical FTD cases characterized by nonspecific histopathological changes (such as neuronal loss, spongiosis and gliosis), two tauopathies [Pick's disease and FTD and parkinsonism linked to chromosome 17 (FTDP-17)], and one ubiquitinrelated disorder, FTD with motor neuron disease (MND) [8,30,41]. This latter form is characterized clinically by the presence of MND with dementia and neuropathologically by the formation of ubiquitin-positive and tau-negative intraneuronal inclusions in hippocampus and subcortical structures [3,7,9,11,27,31,42,46]. However, ubiquitin-positive intraneuronal inclusions and dendrites have also been reported in familial [6,20,24,35] and in a few sporadic FTD cases in the absence of MND [2,15,18,21,22,36,40,47,48] as well as in FTDP-17 cases [17,28,35].…”
Section: Introductionmentioning
confidence: 99%
“…Mochizuki et al (73) reported a 57-year-old man who had dysarthria at age 57 and was anarthric by age 60. Emotional lability was prominent and movements of the tongue were slow.…”
Section: Case 3 Sugihara Et Al (70) Described a 38-year-oldmentioning
confidence: 98%